Isolation of ethanol- and acid-resistant Acinetobacter baumannii from daqu for efficient esterification of acidic Huangshui - Li, Jiacheng; Zou, Yuan; Jiang, Yumei; Guo, Fei; Yang, Lijuan (Frontiers in Microbiology, 2025)
A large amount of highly acidic wastewater, known as Huangshui, is produced during liquor brewing. To improve its utilization rate and achieve resource recovery of liquor by-products. A strain with high esterifying ability was screened from Daqu and identified as Acinetobacter baumannii. The strain exhibited an esterification enzyme activity of (16.79 ± 0.03) U/mL and an esterification capacity of (45.37 ± 0.33) mg/g. It was able to grow normally under conditions of 7% ethanol and pH 4.0, demonstrating strong acid and ethanol tolerance, indicating its potential for preparing a Huangshui esterification solution. Subsequently, Huangshui was esterified using ethanol, caproic acid and Daqu powder prepared with this strain. Analysis of trace components in Huangshui before and after esterification showed that the ethyl caproate content in the esterified Huangshui reached (649.26 ± 2.39) mg/L, which was 13.19 times higher than that before esterification, while ethyl lactate decreased by 15.35%. These results indicate a notable ability to enhance ethyl caproate and reduce ethyl lactate. It is expected that the application of this Huangshui esterification solution could improve the flavor and quality of Non-gxiangxing Baijiu by increasing ethyl caproate and decreasing ethyl lactate, thus providing a reliable experimental basis for the resource utilization of Huangshui.